ANALISIS FRAMING PEMBERITAAN KASUS PULAU REMPANG, PADA MEDIA ONLINE RIAUPOS.CO DAN KOMPAS - Nur Avini; Fajri Ahmad (Busyro: Jurnal Dakwah dan Komunikasi Islam, 2024)
This Research was motivated by clashes between the community and security forces due to the refusal of the Rempang Island community to be relocated because the land there would be used as the Rempang Eco-City area. From this incident, many online media were interested in reporting on the conflict with various views, two of these online media were Riaupos.co and Kompas.com. In obtaining data, the author used a descriptive qualitative method, then the data was obtained from observation and taking the documentation archives in the two online media. This research was conducted using Robert N. Entman's framing analysis technique with four elements, namely Define Problem, Diagnose Cause (Cause of the Problem), Make Moral Judgment (Making Moral Choices) and Treatment Recommendation (Emphasizing Solutions). The results of the analysis obtained are that the define problem element focuses on community action, while Kompas.com focuses on explaining the resolution efforts of various parties. The causes of the problems between the two media both explain that the causes of the clashes started with the community. Regarding moral choices, Riaupos.co explains the incident in detail, while Kompas.com only provides a general description. The solutions from both media both frame problem resolution according to the best viewpoints put forward by various parties.